Impact of American Foreign Policy on the International System - Dana Mohammed Danish Aladdin Sajadi (Eurasian Journal of Management & Social Sciences)
After the end of the second global war the United States aimed to establish a global system founded on its core values of democracy, freedom, multilateralism, and cooperation. This vision aimed to create a more prosperous and secure world where all nations could benefit mutually. However, over time, U.S. foreign policy shifted its course, focusing on shaping the international system to align with its own interests. It increasingly relied on hard power to compel other nations to comply and exert influence. The U.S. became directly and indirectly involved in various regions worldwide as part of its strategy to maintain a hegemonic role and leadership. This paper explores the role of the United States in shaping international affairs through its foreign policy and its impact on the global landscape. The study employed a qualitative research approach and through document analysis to investigate these dynamics.